Hubungan Self efficacy Dengan Kecemasan pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa di UPTD Khusus RSU Haji Medan tahun 2024 - Ainun, Kamaliah; Kristina, Kristina; Gustiani , Winda Sri (Lembaga Dongan Dosen, 2025)
Chronic kidney failure (CKD) is a progressive and irreversible kidney function disorder, where the kidneys experience damage to the parenchyma, resulting in the accumulation of metabolic waste. Based on data in May, as many as 36 people suffering from chronic kidney failure underwent hemodialysis. The purpose of the study was to determine the relationship between self-efficacy and anxiety of chronic kidney failure patients undergoing hemodialysis at the Special UPTD of Haji Medan Hospital in 2024. The type of research used is a type of quantitative research. With a cross sectional approach is a study that explores how and why this health phenomenon occurs. The population in this study is 36 people. The sampling technique uses total sampling. The data collection method uses a questionnaire and a statistical test uses the Chi Square Test. The results of the study were obtained that the value of Self Efficacy was p 0.002 (0.005) and the value of anxiety was p0.000 (0.005). This means that there is a relationship between self-efficacy and anxiety of chronic kidney failure patients undergoing hemodialysis at the Special UPTD of Haji Medan Hospital in 2024. The conclusion of this study shows that there is a relationship between self-efficacy and anxiety of chronic kidney failure patients at the Special UPTD of Haji Medan Hospital in 2024 and it is hoped that services at the hospital can increase education about hemodialysis so that patients are not too anxious when they are about to undergo hemodialysis.